DEVELOPMENT OF STUDENT ACTIVITY SHEET WITH CONNECTING, ORGANIZING, REFLECTING, EXTENDING LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES ON SENIOR HIGH SCHOOL STUDENTS - Bariyah, Khairul; Tjandrakirana, Tjandrakirana; Raharjo, Raharjo (Universitas Negeri Surabaya, 2018)
This study aims to produce LKPD based on communication and collaboration with CORE learning model a decent to improve learning outcomes and Train Communication Skills on students in the subject matter of the Nervous System in Humans. This research have used 4D development model that has been tested on students in class XI IPA 4, XI IPA 5, and XI IPA 6 in SMAN 18 Surabaya with research design one group pretest and posttest design. Research data has been obtained through the method of validation, observation, test, and questionnaire. The results are analyzed descriptively quantitative and qualitative. The results showed that: (a) LKPD with CORE learning model and learning tools developed categorized as valid; (b) the implementation of learning activities is very good; (c) student learning outcomes on the knowledge aspect increases with high criteria; (d) the students provide very positive response to the learning that has been implemented. Based on the analysis and discussion, it is concluded that LKPD with CORE learning model is suitable to be used to improve student learning outcomes on high school students.